Electromagnetic Navigational Bronchoscopy - Port, Jeffrey; Harrison, Sebron (Seminars in Interventional Radiology, 2013)
Despite advances in technology and treatment options, lung cancer remains a deadly disease. National screening programs are being instituted in an attempt to discover lung cancer in high-risk individuals at an earlier stage. Such screening programs invariably discover small peripheral nodules that previously would not have been clinically apparent; the management of such lesions can be challenging. Current diagnostic options such as percutaneous biopsy are effective; however, they are hindered by their risk of morbidity such as pneumothorax. Electromagnetic bronchoscopy (ENB) is an emerging technology that allows the practitioner the ability to both sample and treat small peripheral pulmonary lesions. In experienced centers, ENB provides high rates of diagnostic yield for small lesions and a complication rate significantly lower than that of more conventional diagnostic modalities. Although there are current barriers to its widespread utilization (cost, specialized imaging, technical training), these obstacles will handled similarly to any other emerging technology and will likely not be long-term impediments to its use.
Keywords: lung cancer; pulmonary nodule; electromagnetic bronchoscopy (ENB)